Intraoperative visual experience and preoperative counselling during phacoemulsification under topical anaesthesia - Shakya, Kiran; Pandey, Suprada Pokhrel; Pokhrel, Ram Prasad; Pokhrel, Om Krishna (Journal of Kathmandu Medical College, 2016)
Background: Phacoemulsification surgery using topical anesthesia makes patient experience a multitude of visual sensations. However, it makes cataract surgery safe with the quickest visual recovery. Objective: To find the effect of preoperative counseling about potential intraoperative visual experience during phacoemulsification under topical anesthesia to alleviate fear in patients having cataract surgery. Methods: This non- randomized and non comparative study was carried out in a tertiary care hospital from February 2015 to April 2015. Forty five adult patients underwent cataract surgery (phacoemulsification with foldable intraocular lens implantation) under topical anesthesia using Proparacaine hydrochloride 0.5 % eye drops by a single surgeon. All patients received counseling on the potential intraoperative visual experience during phacoemulsification. A structured questionnaire was used to collect data on socio-demographics, pain, intraoperative visual experiences and their fear. Participants were asked if they experienced visual sensations such as light perception, gush of water and movements during surgery. Results: Nineteen (42.2%) of them were men and 26 (57.8%) were women. Sixty nine percent of the patients were above 60 years. All of them reported having experienced visual sensations during surgery, the most common being light perception (100%), movements of instruments or surgeon’s hands (91.1%) and gush of water (62.2%). One case (4.4%) felt tolerable pain associated with fear (P=0.000) due to these visual experience. Conclusion: Preoperative counseling about the potential intraoperative visual experience during phacoemulsifiaction under topical anesthesia alleviates the visual experience fear in patients having cataract surgery. Journal of Kathmandu Medical College, Vol. 4, No. 2, Issue 12, Apr.-Jun., 2015, Page: 45-49